2016
DOI: 10.1039/c6cp05153g
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of quadrupolar dyes for two-photon absorption: the role of intermolecular interactions

Abstract: We present a theoretical investigation of small aggregates of quadrupolar (A-π-D-π-A or D-π-A-π-D) charge-transfer dyes, with attention focused on the role of intermolecular interactions in determining their optical properties. We tackle the theoretical issue by adopting essential-state models (ESMs), which describe an isolated molecule in terms of a minimal number of electronic states, corresponding to the resonance structures. ESMs quite naturally describe intermolecular interactions relaxing the dipolar app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 86 publications
5
105
0
Order By: Relevance
“…As a result, the absorption spectrum of a suspension of nanoparticles of R‐Me in water has been shown to undergo a noticeably blueshifted absorption maximum, reminiscent of a H‐aggregate spectrum, along with the appearance of a redshifted band (Figure S1 in the Supporting Information) . From a theoretical investigation using essential‐state models (ESMs), Terenziani, Sissa et al. could evidence a H‐type behavior in agreement with the experimental X‐ray diffraction and spectroscopic results.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…As a result, the absorption spectrum of a suspension of nanoparticles of R‐Me in water has been shown to undergo a noticeably blueshifted absorption maximum, reminiscent of a H‐aggregate spectrum, along with the appearance of a redshifted band (Figure S1 in the Supporting Information) . From a theoretical investigation using essential‐state models (ESMs), Terenziani, Sissa et al. could evidence a H‐type behavior in agreement with the experimental X‐ray diffraction and spectroscopic results.…”
Section: Introductionsupporting
confidence: 67%
“…However, fluorescence emission in crystals of R‐Me occurs at much lower energy relative to that of the excimer state in the nonconjugated dimers investigated in this study, which means that more reliable descriptors of the interaction between curcuminoid‐BF 2 chromophores are still needed to reproduce finely the optical properties of these dyes in the solid state. In particular, previous computational studies revealed significant charge‐transfer contributions. Mixing between Frenkel and charge‐transfer excitations is important in determining the optical properties of tightly packed solid‐state assemblies .…”
Section: Discussionmentioning
confidence: 92%
“…Essential-state models( ESMs)p rovide as imple and physically sound description of CT chromophores [54][55][56] and their aggregates, [57][58][59][60][61] and were effective in rationalizing the different propensityt os ymmetry breaking of various families of quadrupolar and octupolar dyes. [28,62,63] ESMsd escribe each dye in terms of am inimal set of basis states, corresponding to the main resonating structures.…”
Section: Essential-state Modelingmentioning
confidence: 99%
“…Further work will be required in the next future to definitively clarify these aspects, a necessary premise to face a robust modelling of the linear and non-linear optical properties of these systems in aggregate form, a topic of large interest in the recent literature. [19] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, they have attracted large interest for different applications as solar cell dyes, [3][4][5][6][7] fluorescent probes, [8,9] photosensitizers for photodynamic therapy, [10][11][12] and nonlinear optical chromophores. [13][14][15][16][17][18][19][20] Figure 1 reports the structure of the simple squaraine dye that will be studied in this contribution, since now on referred to as SQ0. Inspection of the chemical structure suggests that both bi-radical and zwitterionic (charge-transfer, CT) resonance formulas are possible.…”
Section: Introductionmentioning
confidence: 99%